Synthesis and characterization of novel poly (p-methyl styrene) containing azetidine moieties and their optical and semiconducting properties - Erten, Hilmi; Soykan, Cengiz (Elsevier Sci Ltd, 2014)
The p-methyl styrene-based monomer, p-methoxy-3-(1-cyclohexyl) azetidinyl styrene (PMAS) was synthesized by reacting N-cyclohexylazetidinol with p-chloromethyl styrene in tetrahydrofurane solvent at room temperature in the presence of potassium tert-butoxide (t-BuOK). The free-radical initiated polymerization of PMAS was carried out in 1,4-dioxane solution at 70 +/- 1 degrees C using 2,2'-azobisisobutyronitrile (AIBN) as an initiator. The synthesized monomer and homopolymer have been characterized fully by a range of spectroscopic, thermal analysis and SEM analysis techniques. This homopolymer has been converted into a novel salts by reaction with the iodomethane(CH3I) at different times (60, 180, 300 min). The electrical conductivity of the poly(PMAS) salts was measured and the poly(PMAS) salts exhibit the semiconducting behavior. The optical band gap and electrical resistance values of this polymers were obtained to be 3.79, 3.77, 3.82 eV, and 6.63 x 10(8), 7.09 x 10(9), 2.28 x 10(10) Omega, respectively. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: p-Methoxy-3-(1-cyclohexyl) azetidinyl styrene; Quaternerization; Semiconducting properties; Optical properties